The role of social anxiety, the behavioural inhibition system and depression in online gaming addiction in adults. Issue 3 (1st September 2016) - Vanzoelen, Deborah; Caltabiano, Marie L.
This study explored whether adults, who have symptoms of social anxiety or depression, or a temperamental tendency towards having a high behavioural inhibition system (BIS), will be more prone to developing online gaming addiction. Data were collected over a two-month period with a total of 186 participants completing all the online questionnaires (147 university students and 39 Second Life (SL) users), of whom 66 were male (M=34.6, SD=14.15) and 120 were female (M=33.32, SD=12.8). Results of a hierarchical multiple linear regression analysis indicated that combined, social anxiety, a high BIS and depression explained a small amount of variability (9.9 per cent) in gaming addiction, with social anxiety explaining the most variance in the model. Any effect of the BIS was mainly through its impact on social anxiety. Young adult (26–40 years) and middle adult (41–60 years) females represented a higher proportion of problematic gamers in this sample than males. Further research is required into risk factors for addictive gaming, particularly in adult female players.